A PHENOMENOLOGICAL STUDY: NURSES’ EXPERIENCES IN PROVIDING WOUND CARE WITH COMPLEMENTARY THERAPY - Juli Evianna Br Purba; Beres Naibaho; Evi Christin Br Sembiring (Journal of Innovative and Creativity, 2026)
Complementary therapies (CTs) are increasingly used by nurses in wound care, especially in rural settings where cultural practices and limited resources shape clinical decisions. In Indonesia, traditional remedies such as herbal salves and natural compresses are frequently integrated into daily care, yet the lived experiences of nurses delivering such care remain underexplored. Guided by Jean Watson’s Theory of Human Caring, this study aimed to explore how nurses in Tanjung Anom Village, Deli Serdang, experience and perceive their role in providing wound care using complementary therapy. A qualitative, interpretive phenomenological approach was used. Seven registered nurses working in community and primary healthcare settings in Tanjung Anom were purposively selected. In-depth, semi-structured interviews were conducted face-to-face between November and December 2025. Data were analyzed thematically using Braun and Clarke’s six-step framework with the assistance of NVivo 12. Member checking, audit trails, and peer debriefing ensured trustworthiness. Four central themes emerged: (1) Healing Rooted in Culture—nurses embraced traditional therapies as culturally sensitive care; (2) Bridging Two Worlds—nurses navigated between professional training and indigenous knowledge; (3) Care Beyond Wounds—therapies were seen as relational and holistic interactions; and (4) Ethical Tightrope—nurses expressed concerns about safety, legality, and lack of formal protocols. These themes revealed a conceptual model in which nurses act as cultural mediators, integrating complementary care while preserving patient trust and professional ethics. Nurses in rural Indonesia integrate complementary therapies into wound care not merely for efficacy, but as an expression of holistic, culturally responsive nursing. This study highlights the importance of acknowledging and supporting these practices through education, policy development, and ethical frameworks, especially in underserved areas. Complementary wound care should be recognized as a legitimate, relational, and contextually grounded dimension of professional nursing.